2019
DOI: 10.12932/ap-111018-0414
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of periostin and TGF-β1 in the bronchoalveolar lavage fluid of patients with idiopathic eosinophilic pneumonia

Abstract: Background: Periostin is induced in bronchial epithelial cells and fibroblasts by various stimuli including interleukin (IL)-13 and transforming growth factor (TGF)-β 1 , and is involved in allergic diseases such as asthma and atopic dermatitis, playing an important role in tissue remodeling and fibrosis. The role of periostin in the pathogenesis of eosinophilic lung diseases, however, is unclear.Objective: To examine the contribution of periostin to eosinophilic inflammation of the lung in humans, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…It was found that the value of periostin positively correlated with the IL-13 and TGF- β 1. The finding was similar to the research of patients with idiopathic eosinophilic pneumonia, Katoh et al, demonstrating that periostin was induced by IL-13 and TGF- β 1, which accounted for an important role in tissue remodeling and fibrosis [ 44 ]. Moreover, the LVEF was negatively correlated with the IL-13, TGF- β 1, and periostin, which might be caused by the elevated periostin that mediates the progress of myocardial fibrosis, leading to cardiac remodeling.…”
Section: Discussionsupporting
confidence: 88%
“…It was found that the value of periostin positively correlated with the IL-13 and TGF- β 1. The finding was similar to the research of patients with idiopathic eosinophilic pneumonia, Katoh et al, demonstrating that periostin was induced by IL-13 and TGF- β 1, which accounted for an important role in tissue remodeling and fibrosis [ 44 ]. Moreover, the LVEF was negatively correlated with the IL-13, TGF- β 1, and periostin, which might be caused by the elevated periostin that mediates the progress of myocardial fibrosis, leading to cardiac remodeling.…”
Section: Discussionsupporting
confidence: 88%
“…In other words, miR-216a-5p other researches showed that the TGF-β1 signaling participated in the regulation of pulmonary inflammation, 22 and its expression was elevated in the bronchoalveolar lavage fluid of patients with idiopathic eosinophilic pneumonia. 28 Thus, this study inferred that miR-216a-5p might also suppressed the TGF-β1 signaling pathway through modulating TGFBR2. Furthermore, the investigation of the underlying mechanism of miR-216a-5p on LPS-induced inflammation in the human bronchial epithelial cell revealed that miR-216a-5p suppressed LPS-induced inflammation in BEAS-2B cells via regulating TGFBR2.…”
Section: Discussionmentioning
confidence: 66%
“…TGFβ was not significantly correlated with any other soluble markers, although it was grouped with type 2 cytokines. Given the functional role of TGF-β in mucosal immunity and eosinophilic pneumonia, 24,25 a significant elevation of TGF-β in respiratory specimens from severe COVID-19 patients can be indicative of eosinophilic and type 2 mucosal immune responses.…”
Section: Resultsmentioning
confidence: 99%